Myth of Inkarri-Qollari (four narrations) - Müller, Thomas (1984)
The versions of the Myth of Inkarri that Thomas Müller makes known on this occasion, are added to two others that were collected, in the same locality, at the end of the 50s by Oscar Núñez del Prado and Efraín Morote Best. The locality referred to is the Q'eros community, which is reputed to be one of the most traditional in the Andean area and has attracted the interest of many anthropologists, including ourselves.